[Glacial Valley Around Fnjóská River] - Streng, Evelyn Fiedler (1975)
Photograph of a glacial valley and a bridge over the Fnjóská River. A grey, foliage striped mountain sits in the background to the left, a large, dense forest sat in front of it. An arched bridge crosses over the blue river running across the bottom of the photograph. A dirt road leads from a group of people along the right edge of the photograph to the bridge and then continues through the forest from the opposite end of the bridge on the left.